Does family life cycle influence farm households' adoption decisions concerning sustainable agricultural technology? - Fenni Li; Junbiao Zhang; Chunbo Ma (Journal of Applied Economics, 2022)
The literature examining the role played by family life cycle in farm households' decisions to adopt sustainable agricultural technology (SAT) remains scant. To bridge this gap, we evaluate the impact of family life cycle on farm households' adoption of SATs by using multivariate probit regression analyses of survey data from 902 farm households in Hubei Province, China. The results show that most farm households belong to the middle stages of the family life cycle. Straw returning is the most frequently adopted SAT among farm households. Farm households' SAT adoption decisions are closely related to family life cycle. SAT adoption by farm households differs at each family life cycle stage. Based on this finding, when stimulating SAT adoption, the government should consider the different capital endowments and needs of farm households at different family life cycle stages as well as conduct differential and targeted technology promotion measures.
Keywords: 330; adoption decision; Family life cycle; multivariate probit model; sustainable agricultural technologies